Toxicity and teratogenicity effects of valproic acid on zebrafish (Danio rerio) embryos in relation to autism spectrum disorder - Saleh Hodin, Nur Atikah; Chong, Siok Geok; Abu Bakar, Noraini; Mohd Fahmi, Muhammad Syafiq Akmal; Ramlan, Nurul Farhana; Zulkifli Hamid, Nik Nur Aini Zulaikha; Mohd Fadzar, Muhammad Syuqor Iqbal; Zulkifli, Abdul Rahman; Norazhar, Anis Irfan; Mastuki, Siti Nurulhuda; Mohd Faudzi, Siti Munirah; Wan Ibrahim, Wan Norhamidah; et al. (John Wiley, 2023)
Valproic acid (VPA) is a widely prescribed antiepileptic drug with various medicinal efficacies. Accumulated evidence implied that prenatal exposure to VPA is highly associated with autism spectrum disorder (ASD). In this study, the zebrafish were exposed to a set of VPA concentrations (0, 5, 10, 20, 40, 80, 160, 320, 640, 1280, and 2560 μM) at 5 h post fertilization (hpf) to 120 hpf. The adverse effects of VPA were extensively studied through the evaluations on the mortality, heartbeats, spontaneous tail coiling, and hatching rate. Morphological observations were conducted at 120 hpf, following the exposure termination. Basic locomotor responses and anxiety-like behavioral alterations evaluated for behavioral impairments are the hallmark feature of ASD. The exposure to VPA at teratogenic concentrations reduced the aforementioned parameters in a dose-dependent manner (p ≤.05). At the selected non-teratogenic concentrations of VPA, the treated larvae demonstrated profound alterations of basic locomotor responses. No significant changes of anxiety and thigmotactic behaviors were observed on the VPA-treated fish compared to the control (p ≥.005). This study depicted that embryonic zebrafish exposure to VPA produced significant toxicity and teratogenicity effects as well as the alterations of basic behavioral responses. Overall, this study provides a fundamental insight of the toxicity effects at morphological and behavioral levels to facilitate the understanding of ASD mechanisms at different molecular levels.